2019
DOI: 10.31234/osf.io/szr3f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organizational and Individual Safety Factors in Work on Chemical Tanker Vessels

Abstract: Chemical tanker vessels are at risk for large-scale accidents due to the nature of their cargo and operating conditions, challenging environments as well as general maritime hazards. To counteract such hazards, the ship-owning company works on maintaining safety at the organizational level, and the captain instantiates safety regulations on the interpersonal level. The crew members are expected to maintain safety by having accurate situation awareness, and beneficial safety attitudes and behaviour. We pre-regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…A previous analysis of self-reported variables in the current dataset (Hjellvik et al, 2019) has shown that organizational factors and safety attitudes predict safety behaviour. The self-reported statements about attitudes, cognition and safety policies were used as indicators for the crew's self-reported safety behaviour.…”
Section: 2: Research Needs and Current Studymentioning
confidence: 68%
See 4 more Smart Citations
“…A previous analysis of self-reported variables in the current dataset (Hjellvik et al, 2019) has shown that organizational factors and safety attitudes predict safety behaviour. The self-reported statements about attitudes, cognition and safety policies were used as indicators for the crew's self-reported safety behaviour.…”
Section: 2: Research Needs and Current Studymentioning
confidence: 68%
“…However, all self-report measures have limitations that bias the results and limit the conclusions and causal inferences. The object of the current study is therefore to investigate if factors previously identified as safety critical (see Hjellvik, Aga, & Saetrevik, 2019) have an impact on behaviour categorized as unwanted or dangerous in the same population where data were collected.…”
Section: : Introductionmentioning
confidence: 99%
See 3 more Smart Citations